Analysis of Triacylglycerols in Castor Oil Through Liquid Chromatography–Mass Spectrometry Based on Fourier Transform–Ion Cyclotron Resonance–Mass Spectrometry and Gas Chromatography–Mass Spectrometry. (6th October 2018) - Du, Jialin; Gong, Can; Pei, Xingli; Zhao, Haiyan; Xu, Xu
Abstract: Castor oil is a traditional Chinese medicine containing a chemically complex mixture of triacylglycerols (TAGs). Herein, the TAGs in castor oil were analyzed in detail. First, the fatty acid composition of castor oil was examined via methylated derivatisation followed by gas chromatography–mass spectrometry (GC–MS). Then, using the fatty acid composition data, liquid chromatography–mass spectrometry (LC–MS) was applied to analyze the composition and relative content of TAGs. Nine TAGs were identified, wherein triricinolein (RRR) constituted ~81% of the total TAG content based on the peak areas. However, the TAGs in castor oil contain hydroxyl groups, which are incompatible with the equivalent carbon number (ECN) rule. Thus, an extended-ECN rule was expressed as E-ECN = CN (carbon number)—2·DB (double-bond number)—6·OH (hydroxyl group number) to characterize the retention of hydroxyl-containing TAGs in HPLC using a C18 column. Moreover, hydroxyl-containing TAGs may become dehydrated when analyzed using atmospheric pressure chemical ionization (APCI), which was confirmed via APCI Fourier transform–ion cyclotron resonance–mass spectrometry (FT–ICR–MS). Thus, the TAGs in castor oil were accurately identified through LC–MS together with FT–ICR–MS and GC–MS.